HSE–OECD International Research Conference «Foresight for Innovative Responses to Grand Challenges» - Нет, Нет (Foresight and STI Governance, 2012)
In recent years innovation has been under the scrutiny of international development institutes. Innovation is considered as a key driver to foster economic growth and overcome crises. Innovation processes are among the most troubled fields of governance. Today policy-makers and experts face two basic challenges — increasing the complexity of the global context and broadening the range of issues in order to improve the implementation of innovation strategies. This fundamental issue was the focus of discussions held on mid-October 2012 under the HSE ISSEK and OECD joint conference, which coincided with ISSEK’s 10-year anniversary. The agenda included three sessions: STI Policy Futures; Responses to Grand Challenges; Strategic Intelligence Tools. Presentations were made by experts from OECD, University of Manchester (UK), University of Ottawa (Canada), Fraunhofer Institute for Systems and Innovation Research (Germany); Georgia Technology University (USA), Science and Technology Policy Institute (Republic of Korea), Higher School of Economics etc. The following issues were discussed: future of STI policy; STI policy agenda for Russia; applying Foresight to setting priorities for STI policy; S&T responses to Global Challenges; and new tools of Foresight. The participants concluded that that there is a necessity to revise policy instruments established in the last century as well as consolidate resources and ideas in order to meet accelerating global changes. It is unlikely that global challenges have ultimate solutions. However tackling them necessitates purposeful, joint and continuous efforts by stakeholders. Foresight as a tool enabling creation of interdisciplinary knowledge and reconciling stakeholders’ interests together can play a crucial role in this process.